Interpersonal values and self-concept in environmental engineering and business administration students of a public state university - Sánchez P., Rubén (2014)
The present research study aims to relate interpersonal values and self-concept. It is descriptive; correlational; comparative and with a non-experimental design. The sample consisted of 217 public state university students; both male and female; in their first; third and fifth cycles of Environmental Engineering and Business Administration careers. Fernando García and Gonzalo Musitu Self-Concept Questionnaire AF5 Form; validated by Sandoval (2009) and Portilla (2011); and Leonard V. Gordon Interpersonal Values Questionnaire (SIV); adapted by Higueras (1972) and Perez (1987); were the instruments applied. Results showed that there exist correlations between Support and Conformity Values and GeneralSelf-Concept. In a more specific analysis; no relationship between any Interpersonal Value and Family Self-Concept was found. Furthermore; significant differences between Physical and Emotional Self-Concept and Leadership Interpersonal Value were found. On the other hand; there were not statistically significant differences between Interpersonal Values and Self-Concept concerning their professional careers.